Analysis of airflow around ski-jumper and evaluation of take-off motion - Yamamoto, K.; Kawahatsu, K.; Uesugi, T.; Shimooka, T.; Shimizu, K. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: The purpose of this study was to examine the effect of airflow condition around the jumper's back on the aerodynamic forces in ski-jumping take-off, and to propose an appropriate index to evaluate the take-off motion with an aerodynamic analysis.